1980
DOI: 10.1159/000232472
|View full text |Cite
|
Sign up to set email alerts
|

Allergenicity of Major Component Proteins of Soybean

Abstract: Allergenic activities of major component proteins of soybean 11S-, 7S- and 2S-globulins were examined by the radioallergosorbent test (RAST) and by RAST inhibition experiments with the sera from soybean-sensitive patients. The reactivity with specific IgE antibody was found in all fractions. There was considerable cross-reactivity among three fractions, and 2S-globulin had the highest allergen potency to inhibit the RAST against 11S-, 7S- and 2S-globulin. When the fractions were heat-treated at 80, 100 and 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
65
2
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(71 citation statements)
references
References 12 publications
3
65
2
1
Order By: Relevance
“…This is in contrast with data reported by Shibasaki et al (1980) showing that 2S-globulin inhibitor could inhibit 90% of the RAST against 2S, 7S and 11S globulins, suggesting that 2S-globulin is the most potent allergen of the soybean globulins. On the other hand, Ogawa et al (1991) suggested that the 7S fraction is a main allergenic soy protein fraction.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This is in contrast with data reported by Shibasaki et al (1980) showing that 2S-globulin inhibitor could inhibit 90% of the RAST against 2S, 7S and 11S globulins, suggesting that 2S-globulin is the most potent allergen of the soybean globulins. On the other hand, Ogawa et al (1991) suggested that the 7S fraction is a main allergenic soy protein fraction.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study with the 2S, 7S and 11S soy protein fractions we used 50 μg of protein for the initial immunization of mice followed by 5 mg booster of each soy protein fraction for the PCA test. These differences of experimental protocols could lead to the different results found in our experiments when compared with those of Shibasaki et al (1980).In conclusion, our study indicated that the 7S soy protein fraction is allergenic and immunogenic in mice which can be helpful for those interested in the field of allergic reactions to soy-derived foodstuffs. …”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Sequence homology has been reported between these allergens and the thiol proteinase family [17], and with the 49 Detection and identification of a soy protein component that cross-reacts with caseins from cow's milk allergen Der p1. The 11S fraction, or glycinin, has also been characterized as a major soybean allergen involved in food hypersensitivity reactions [13,18]. Our investigation aimed to analyse a possible in vitro crossreactivity between CM and soybean proteins.…”
Section: Introductionmentioning
confidence: 99%